Alternative investments: valuation of wine as a means for portfolio diversification - Jurevičienė, Daiva; Jakavonytė, Agnė (Business: Theory and Practice, 2015)
This article analyses wine as an alternative investment tool and its relevance for investment portfolio diversification. Advantages and disadvantages of alternatives, benefits and weakness and peculiarities of investing in wine are systemised. In addition, the article looks at statistical data analysis of fine wine market and compares wine with other investment tools. The examination is based on three investment instruments: US equities (using S&P 500 index), bonds (using US 20-Year treasury constant maturity rate/DGS20) and wine (based on Fine Wine Investable index) using 1993–2012 (end of year) data. The investment portfolios made with two and three above-mentioned investment tools basing on H. Markowitz’s investment portfolio theory and effective curves are presented. It was found that return on investments only from equities and bonds or wine and one of these traditional instruments are signally less than from the investment mix of all three tools. Furthermore, portfolios made only from equities and bonds provide the lowest return compared to others. Choosing from two investments portfolios, results of bond/wine portfolios propose higher return with the same risk level compared to equities/wine portfolio. Consequently, despite some slowdown of wine index during financial crises, wine relevance for portfolio diversification in post crises period was proved.